Participation and Activity Inventory for Children and Youth (PAI-CY): Translation and Cultural Adaptation to European Portuguese - Ana Isabel Ferreira; Maria Raquel Santana; Cláudia Quaresma; Carla Quintão (Brain Sciences)
Introduction: Visual skills have a significant impact on an infant’s development and participation. In Portugal, although the public health system is organized to support citizens with visual impairment, it lacks translated and culturally adapted assessment tools. Knowing that a comprehensive assessment is crucial for early diagnosis and that it improves an infant’s participation in daily life, the aim of the present article is to present the translation and cultural adaptation of the Participation and Activity Inventory for Children and Youth (0–2 years) into European Portuguese. Methods: To achieve the objective, methodological guidelines were followed, and six different stages were implemented, including translation, synthesis, back translation, revision by an expert committee, pretesting in a representative sample, and submission and appraisal of all written reports by developers to the author’s tool. The whole process was previously approved by an Ethics Committee. Results: A Portuguese version of the Participation and Activity Inventory for Children and Youth (0–2 years) was obtained based on the English version of PAI-CY (0–2 years) with the participation of four independent translators, five experts, and twenty parents filling out the pretest version. The results of the expert committee showed that 99.40% were in favor of the proposed translation. Additionally, the inventory pretesting reveals a clarity PAI-CY validity index of 1, a relevance PAI-CY validity index of 0.98, and a global validity index of 0.99. Conclusions: The Participation and Activity Inventory for Children and Youth (0–2 years) has now been translated and culturally adapted into European Portuguese, guaranteeing its content validity. To use the tool in Portugal with certainty it is necessary to implement the tool validation. The process to investigate the psychometric properties of the questionnaire is being prepared.